The relationship between platelet–lymphocyte ratio and severity of erectile dysfunction. Issue 2 (28th December 2015) - Akbas, Alpaslan; Gulpınar, Murat Tolga; Sancak, Eyüp Burak; Gunes, Mustafa; Ucar, Murat; Altok, Muammer; Umul, Mehmet
Abstract: The prognostic importance of platelet–lymphocyte ratio (PLR) is already known for various artery diseases. In this study, the relationship between PLR and severity of erectile dysfunction (ED) is examined in patients with impotence. The data from patients suffering from erection problems was screened retrospectively. Detailed medical history, age, International Index of Erectile Function‐5 (IIEF‐5) scores, fasting blood glucose, lipid, whole blood count, and hormone profile values were examined. Patients with no ED were selected as the control group. All men answered the IIEF‐5 questions and were then classified according to their scores. Patients were determined to have severe ED (scores 5–7), moderate ED (scores 8–16), or mild ED (scores 17–21). An IIEF‐5 score greater than 21 was accepted for the control group. The PLR values from both patient and control groups were evaluated. Demographic data were similar in both groups. Mean PLR value was 104 in control and 118 in the patient group ( p < 0.001). PLR value increased depending on the severity of ED. Mean PLR values were 108 in mild, 116 in moderate, and 130 in severe ED groups. Compared with the control group, this value was statistically significant for patients with moderate and severe ED ( p = 0.04 and p < 0.001). PLR showed weak negative but significant correlation with IIEF‐5 scores ( r = −0.27 and p < 0.001). The PLR value was found to be higher in patients with ED. PLR value may be related to ED and its severity in patients with impotence.